Internal audit information system (IAIS) for internal audit department of Golden Hope Plantation Berhad - Saaid@Said, Suzari (2005)
Internal Audit Department (IAD) of Golden Hope Plantations Berhad (GHPB) current manual performance monitoring is unable to systematically control and monitor each executive audit visits, audit report issuance, department’s monthly performance and categorize the audit findings according to non-compliance and process improvement. Internal Audit Information System (IAIS) is the proposed solution developed to computerize the current manual system. This will speed up the time and reduce the use of resources (manpower and cost). Object-Oriented Software Engineering (OOSE) is the technique used for this IAIS software development project. IAIS is an in-house developed system that is developed with a minimum cost. Any maintenance or trouble-shooting will be carried out by internal personnel. Implementing IAIS involves building a database thus helping the department to handle large amount of data, satisfy multiple users in using the same system concurrently, making the information retrieval and data input faster, and provide greater accuracy. Redundant record keeping is reduced or eliminated. IAIS will also assist the process of submitting the KPI monthly performance report to the KPI’s Committee every month end. IAIS will also indirectly assist management in evaluating each executive’s performance in IAD throughout the financial year and provide an indicator for bonus and increment. The monetary losses for each audit visit will also be identified and calculated. In line with the GHPB ICT Strategic Directions, IAIS will be an IAD’s effort to support the GHICT master plan in enhancing business productivity and efficiency using ICT tools through computerizing IAD’s process of keeping track the entire audit visits and duration reports issued to the auditee, monitor executive/department monthly performance and categorize the audit findings.